A triphosphate tunnel metalloenzyme from pear (PbrTTM1) moonlights as an adenylate cyclase - Yuan, Ye; Liu, Yuye; Chen, Shuangjiang; Wang, Lili; Wang, Lixin; Niu, Yahong; Zhao, Xin; Zhao, Zhihui; Liu, Zhiguo; Liu, Mengjun (Frontiers in Plant Science, 2023)
Adenylyl cyclase (AC) is the vital enzyme for generating 3′,5′-cyclic adenosine monophosphate (cAMP), an important signaling molecule with profound nutritional and medicinal values. However, merely a dozen of AC proteins have been reported in plants so far. Here, a protein annotated as triphosphate tunnel metalloenzyme (PbrTTM1) in pear, the important worldwide fruit plant, was firstly identified to possess AC activity with both in vivo and in vitro methods. It exhibited a relatively low AC activity but was capable of complementing AC functional deficiencies in the E. coli SP850 strain. Its protein conformation and potential catalytic mechanism were analyzed by means of biocomputing. The active site of PbrTTM1 is a closed tunnel constructed by nine antiparallel β-folds surrounded with seven helixes. Inside the tunnel, the charged residues were possibly involved in the catalytic process by coordinating with divalent cation and ligand. The hydrolysis activity of PbrTTM1 was tested as well. Compared to the much higher capacity of hydrolyzing, the AC activity of PbrTTM1 tends to be a moonlight function. Through a comparison of protein structures in various plant TTMs, it is reasonable to speculate that many plant TTMs might possess AC activity as a form of moonlighting enzyme function.